1997
DOI: 10.1557/proc-483-285
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown Degradation Associated With Elementary Screw Dislocations In 4H-SiC P+N Junction Rectifiers

Abstract: It is well-known that SiC wafer quality deficiencies are delaying the realization of outstandingly superior 4H-SiC power electronics. While efforts to date have centered on eradicating micropipes (i.e., hollow core super-screw dislocations with Burgers vector > 2c), 4H-SiC wafers and epilayers also contain elementary screw dislocations (i.e., Burgers vector = 1c with no hollow core) in densities on the order of thousands per cm 2 , nearly 100-fold micropipe densities. This paper describes an initial study into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Pixels that exhibit trap-to-band tunneling in those devices may show a soft breakdown in the I-V curves, followed by the onset of trap-to-band tunneling. Similar behavior has been observed by other authors in 4H-SiC 25,26 and Silicon 27 diodes caused by screw dislocations and stacking faults respectively. The soft breakdown is caused by traps that become electrically active at a certain "threshold voltage".…”
Section: Dark Current Theorysupporting
confidence: 90%
See 1 more Smart Citation
“…Pixels that exhibit trap-to-band tunneling in those devices may show a soft breakdown in the I-V curves, followed by the onset of trap-to-band tunneling. Similar behavior has been observed by other authors in 4H-SiC 25,26 and Silicon 27 diodes caused by screw dislocations and stacking faults respectively. The soft breakdown is caused by traps that become electrically active at a certain "threshold voltage".…”
Section: Dark Current Theorysupporting
confidence: 90%
“…The soft breakdown is caused by traps that become electrically active at a certain "threshold voltage". The soft breakdowns shown in Neudeck et al 25 and Ravi et al 27 were not uniform, and showed no correlation between the onset of the soft breakdown and the trap density since the traps associated with dislocations may have different threshold voltages at which they become electrically active. Bacon (2006) 5 introduced a variable trap density to parametrically fit the soft breakdown and is given by…”
Section: Dark Current Theorymentioning
confidence: 91%
“…High-quality, high-purity 4H-and 6H-SiC commercial wafers are sawn and polished from boules that are grown by the physical vapor transport process. Defects found in SiC wafers are discussed by Neudeck [57]. Different orientations are also available; typical orientations are basal plane or slightly misoriented from the basal plane by an off cut (giving rise to a vicinal-like geometry) toward either the (1100) or (1 100) directions for various angles, e.g., 8 .…”
Section: Preparation Of Sic For Graphene Synthesismentioning
confidence: 99%
“…Such filamentary behavior has already been observed in the context of highpower SiC p-i-n devices. 24,25 …”
Section: ͑14͒mentioning
confidence: 99%